Microsatellite identification associated with resistance to the mite Mononychellus tanajoa (Acari: Tetranychidae) - MACEA-CHOPERENA, ELIANA DEL PILAR; OSPINA, CESAR; FREGENE, MARTIN; MONTOYA-LERMA, JAMES; BELLOTTI, ANTHONY C. (Revista Colombiana de Entomología, 2012)
The development of the cassava genetic map has promoted research such as the finding of genes associated with the resistance of pests that diminish the production and quality of the crop. Molecular tools, such as markers can facilitate the identification of the genes that dominate resistance to pests this is the specific case of the presence of resistance to the green mite Mononychellus tanajoa (CGM) in cassava (Manihot esculenta). Initially, at International Center for Tropical Agriculture CIAT, individuals populations of backcrosses (BC1), lineage of four denominated families CW, were identified. These BC1 were identified and categorized according to 1-5 scale of damage reported by the Entomology Program at International Center for Tropical Agriculture. Resistant and susceptible individuals were identified. A total of 500 microsatellite markers were evaluated using the bulk segregant analysis (BSA). Five of them expressed polymorphism and showed significant differences between parental and contrast groups and three markers, namely, SSRY 11, SSRY 346 and, NS 1099. Statistical analysis revealed that markers NS 1099 and NS 346 displayed the highest association between resistance and the individuals of families CW 67, CW 66 and CW 67, respectively. On the basis of these results we can recommend the use of microsatellite for further analysis in other populations in order to achieve the of some chromosomal regions conferring resistance to green mite cassava.